2014
DOI: 10.1002/alr.21297
|View full text |Cite
|
Sign up to set email alerts
|

The fungal microbiome in chronic rhinosinusitis: richness, diversity, postoperative changes and patient outcomes

Abstract: This is the first study to use a highly sensitive pyrosequencing technique to reveal the true diversity of fungi in the sinuses of CRS patients and postoperative changes in richness. The presence of Malassezia, a genus not previously described in the sinuses, is of great interest, and its potential as a disease modifier should see further investigation given its association with atopic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
78
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 34 publications
0
78
0
1
Order By: Relevance
“…It is noteworthy that both fungi and viruses can affect the nasal bacterial microbiome and trigger the immune system [22]. Recent studies that used organismspecific primers for PCR analyses of fungi were able to give a more complete picture of the fungal microbiome (mycobiome) in the nose [14,15]. Future studies are needed to study the nasal mycobiome and virome in relation to allergic diseases, with a focus on the potential functional pathways of these microorganisms.…”
Section: Concerns and Areas Of Unmet Research Needs In The Nasal Micrmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that both fungi and viruses can affect the nasal bacterial microbiome and trigger the immune system [22]. Recent studies that used organismspecific primers for PCR analyses of fungi were able to give a more complete picture of the fungal microbiome (mycobiome) in the nose [14,15]. Future studies are needed to study the nasal mycobiome and virome in relation to allergic diseases, with a focus on the potential functional pathways of these microorganisms.…”
Section: Concerns and Areas Of Unmet Research Needs In The Nasal Micrmentioning
confidence: 99%
“…Use of culture-independent methods, especially analyzing the 16S ribosomal RNA of bacteria, showed evidence for a rich and diverse community of bacteria in the nose that is shifted significantly in the presence of allergic diseases [1][2][3][5][6][7][13][14][15]. With the use of current complex methods, we can not only predict the abundance of each taxa and their community structures but also predict and compare their functions.…”
mentioning
confidence: 99%
“…Thus far, most microbiome studies have focused on bacteria (Turnbaugh et al 2009;Arumugam et al 2011;Gajer et al 2012;Human Microbiome Project Consortium 2012), although some include fungi (Paulino et al 2006;Findley et al 2013;Cleland et al 2014;Willger et al 2014) and viruses (Reyes et al 2010;Minot et al 2011;Wylie et al 2012Wylie et al , 2014De Vlaminck et al 2013). Viruses are particularly understudied, in part due to the challenges of assessing their presence in clinical samples.…”
mentioning
confidence: 99%
“…Species, including Candida, Aspergillus and Mucor, differ in studies and may even be found in asymptomatic control subjects. [12] Employing multiplex polymerase chain reaction for respiratory viruses, viral nucleic acid sequences have been found in 64% of sinus scrapings and 50% of nasal lavage samples in a chronic rhinosinusitis group of patients. [13] These were significantly higher than in controls (30% and 14% in scraping and lavage, respectively) and rhinovirus was the most frequently detected virus.…”
Section: The Fungal and Viral Microbiome In Chronic Rhinosinusitismentioning
confidence: 99%